Investigation and simulation of the age-dependent behaviour of an aluminium alloy under thermomechanical loading. (December 2020) - Seisenbacher, B.; Winter, G.; Grün, F.
Abstract: A constitutive material model, which predicts the material behaviour of an Al–Si–Mg–Cu alloy under thermomechanical load, is proposed. Moreover, an ageing model is used to simulate the ageing behaviour, which also affects the hardening parameters. A new strategy for determining the material parameters is proposed, and a new testing concept for investigating the ageing properties of materials is presented. Thermomechanical fatigue tests are used to validate the material model. The results of the simulations show that it is possible to determine the material parameters based on low-cycle fatigue, relaxation, and ageing tests such that a cycle-by-cycle simulation of thermomechanical fatigue tests is possible. Finally, a comparison of the simulation and test results show a good agreement. Highlights: A new ageing test concept was developed. The ageing behaviour of an aluminium alloy was investigated and modelled based on the results of the new test strategy. An elastic-viscoplastic model is coupled with an ageing model. A strategy for the determination of the material parameters of an elastic-viscoplastic material model is presented. It could be shown that the simulations are in good agreement with the test results, taking ageing into account.